Relationships between intramuscular fat percentage and fatty acid composition in M. longissimus lumborum of pasture-finished lambs in New Zealand. (November 2021) - Realini, C.E.; Pavan, E.; Purchas, R.W.; Agnew, M.; Johnson, P.L.; Bermingham, E.N.; Moon, C.D.
Abstract: This paper reports relationships between fatty acids (FAs) and intramuscular fat (IMF)% in M. longissimus lumborum samples from 108 pasture-fed ewe lambs. Samples ranged in IMF from 1 to 6%. Relationships between %FA with total IMF% were mainly linear with percentages of saturated and monounsaturated FAs (MUFA), including trans -FAs, increasing and polyunsaturated FAs decreasing as IMF% increased. Normalized FA content data at 5.5% relative to 1.5% IMF, showed the highest relative increase for C14:0 as rates of endogenous synthesis increase with higher IMF deposition. This can be related to enhanced C12:0 elongation and lower rates of C14:0 desaturation, supported by a preferential desaturation of C18:1 trans -11 and C18:0 compared with C14:0 and C16:0 as IMF increased. The greatest normalized increase after C14:0 was anteisoC17:0 followed by other branched chain FAs and then trans -MUFA and C18:2 cis -9, trans -11. Finally, C22:6 and C22:5 showed higher relative increase than C20:5 indicating greater rates of elongation and desaturation past C20:5 at higher levels of fatness. Highlights: Changes in fatty acids (FA) with increasing lamb intramuscular fat were reported. Results confirm the increased saturation at higher levels of fatness. C14:0 showed the highest relative increase followed by anteiso-C17:0 and other BCFA. trans -Monounsaturated FA and C18:2c9, t11 showed the next greatest relative increase. C22:6n-3 and C22:5n-3 showed higher relative increase than C20:5n-3 with increased fatness.